Protection of rights of adopted children in relation to duties of adoptive parents under the law in Malaysia - Mohd, Azizah (Routledge, 2011)
The relationship between parents and children can be established either through "blood," marriage, or adoption. This relationship gives rise to certain rights and obligations. This article seeks to examine the protection of those rights of adopted children under the law in Malaysia and to evaluate the extent to which the law protects the rights of adopted children. This article will also examine whether the law in Malaysia imposes certain duties on the adoptive parents in fulfilling such rights.